2003
DOI: 10.1242/jeb.00583
|View full text |Cite
|
Sign up to set email alerts
|

Blubber and buoyancy: monitoring the body condition of free-ranging seals using simple dive characteristics

Abstract: With the development of time depth recorders (Kooyman, 1965) and satellite, radio and acoustic telemetry (e.g. Fancy et al., 1988;Fedak, 1992;Fedak et al., 1983;McConnell, 1986), it is now possible to study the behaviour of many free-ranging marine organisms. Although these data have provided new insights into the foraging ecology of marine species, there are still limitations in the types of information that can be collected. Specifically, direct observation or recording of feeding events is often impossible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
331
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(339 citation statements)
references
References 65 publications
8
331
0
Order By: Relevance
“…Indirect measurements have suggested that the depth where gas exchange ceases is between 30m (Falke et al, 1985) and 70m (Ridgway and Howard, 1979), but direct measurements of animals diving with a lung volume of only 18% of TLC indicate that complete shunt may not occur until a depth of 170m (Kooyman and Sinnett, 1982). Studies of maximal depth of neutral buoyancy, which has to be at a depth less than atelectasis (Biuw et al, 2003;Skrovan et al, 1999;Williams et al, 2000), agree with the pulmonary shunt data published by Kooyman and Sinnett showing that the collapse occurs at depths below 100m (Kooyman and Sinnett, 1982). Our results using the hyperbaric chamber suggest these last estimates have worth.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect measurements have suggested that the depth where gas exchange ceases is between 30m (Falke et al, 1985) and 70m (Ridgway and Howard, 1979), but direct measurements of animals diving with a lung volume of only 18% of TLC indicate that complete shunt may not occur until a depth of 170m (Kooyman and Sinnett, 1982). Studies of maximal depth of neutral buoyancy, which has to be at a depth less than atelectasis (Biuw et al, 2003;Skrovan et al, 1999;Williams et al, 2000), agree with the pulmonary shunt data published by Kooyman and Sinnett showing that the collapse occurs at depths below 100m (Kooyman and Sinnett, 1982). Our results using the hyperbaric chamber suggest these last estimates have worth.…”
Section: Discussionmentioning
confidence: 99%
“…the seal is passively drifting through the water column), (iii) be longer than 20% of the total duration of the dive, and (iv) have little variance in depth change rate during the entire drift phase (i.e. mean-squared residual should be less than 5 m 2 as per Biuw et al [27]). After running the automated algorithm, we excluded 5.3 + 5.8% (mean + s.d.)…”
Section: (Iii) Estimating Seal Buoyancymentioning
confidence: 99%
“…The total buoyancy of breath-hold divers changes with depth owing to residual air in the lungs, but this effect is reduced at greater depths because air volume decreases with depth following Boyle's law [27]. To minimize the effect of gases on buoyancy, we only used data from depths 100 m or more, as per Aoki et al [23], because in this study we focused not on the effect of residual air but on the effect of body density on swimming costs.…”
Section: (B) Data Analysis (I) Dive Phase Definitionmentioning
confidence: 99%
See 2 more Smart Citations